Características de história de vida de árvores do Cerrado direcionando o futuro e a adaptação aos impactos das mudanças climáticas - Côrtes, Lara Gomes (2013)
The speed of climate change nowadays brings unprecedented challenges to biodiversity conservation. As environmental conditions are important factors in determining the geographical distribution of species, the latter should change their distribution with changes in climate, rearranging communities with gains and losses of species. Aiming to identify vulnerabilities and propose proactive conservation to increase the adaptation of species to climate change we did an approach with species distribution models, an essential tool to predict the species potential distribution in different climatic scenarios. An important understanding in this changing scenario is the knowledge of what life history traits may make species more susceptible to changes in climate and then, may be possible, if such characteristics are related to specific environmental conditions, defining the ecological niche breadth of species as well as their geographic distribution. We sought to identify whether simple life history traits of trees occurring in the Cerrado could be related to the size of the niche and distribution area, and if the species with characteristics associated with a small area distribution and restrict niche breadth would be more predisposed to extinction due to climate change. It was found that the evergreen generalist species have lower potential distributions, evergreen species from broad sense cerrado have smaller latitudinal ranges and height proved to be related to the geographic distribution of broad sense cerrado species. Still trying to identify potential impacts on biodiversity and ecosystem function, assuming the environmental conditions as selective filter of species with life history traits that guarantee a higher performance in a new climate, it was tested if climate change reduces the functional diversity of communities in sub-basins of the Cerrado. There was a large reduction in richness, but an increase in functional diversity, since most communities lost species functionally redundant, but which can act as an insurance against loss of ecosystem functions. Thus, the future communities will be more vulnerable to other disturbances, such as habitat loss and fragmentation. In this context, proactive a that can increase the connectivity of ecosystems will be essential for the biodiversity conservation to climate change. Thus, we propose a systematic planning of restoration to complement the establishment of protected areas and, simultaneously, selected areas of lower socioeconomic conflict and climate stability. The restoration should be understood as an important proactive conservation action in a changing world that is full of increasingly fragmented ecosystems as the Brazilian Cerrado.